Emotional Attitude to School and Self-Attitude in High School Students of Different Sex and Age - Vartanova, I.I. (Psihologičeskaâ nauka i obrazovanie, 2020)
The aim of this work was to study (taking into account gender and age) the relationship between emotional attitude to learning activity and self-attitude in high school students. The following parameters were revealed separately for groups of boys and girls: 1) the structure of the emotional attitude to the values of school life (by factor analysis of assessments obtained with the Semantic Differential scale); 2) the indicators of self-attitude (according to the technique by S.R. Pantileev); 3) the correlations between the selected factors and the parameters of self-attitude. The study involved students of 9—11 grades (14—17 years old) from two Moscow schools. A total of 346 people were surveyed; the subjects were divided into 4 groups: younger groups (8—9 grades, 14—15 years old) boys (73) and girls 76), older groups (grades 10—11, 16—17 years old) of boys (98) and girls (99); both techniques were used in 217 students: younger groups of boys (41) and girls (49), older groups boys (63) and girls (66).As it was found, with age there is a tendency to change the semantic content of some motives — for boys in the field of status motivation, and for girls in the field of learning motivation. In girls, various types of emotional and motivational attitudes toward learning are more consistent with the parameters of self-attitude. At the same time, among younger boys motivation of duty and recognition is closely related to self-attitude, whereas in older boys the latter is related only to learning and cognitive motivation. В статье редставлены результаты работы, направленной на изучение (с учетом пола и возраста) эмоционального отношения к учебной деятельности и самоотношения старшеклассников в их взаимосвязи. Отдельно для групп мальчиков и девочек выявлялись: 1) структура эмоционального отношения к ценностям школьной жизни с помощью факторного анализа оценок по методике семантического дифференциала; 2) показатели самоотношения по методике С.Р. Пантилеева; 3) корреляционные взаимосвязи выделенных факторов с параметрами самоотношения. Исследовались школьники 9—11-х классов (14—17 лет) двух школ г. Москвы; всего опрошено 346 человек, которые были разделены на 4 группы: младшие группы (8—9-е классы, 14—15 лет) мальчиков (73) и девочек (76), старшие группы (10—11-е классы, 16—17 лет) мальчиков (98) и девочек (99); в том числе по двум методикам одновременно 217 учеников: младшие группы мальчиков (41) и девочек(49), старшие группы мальчиков (63) и девочек (66).Описана половая специфика взаимосвязей эмоционально-мотивационного отношения к учебе и параметров самоотношения. Обнаружено, что у девочек эмоционально-мотивационное отношение к учебе в большей степени согласованно с параметрами самоотношения; с возрастом происходит изменение смыслового содержания некоторых мотивов — для мальчиков в сфере аффилиативно-статусной мотивации, а для девочек в сфере самоутверждающе-учебной мотивации. Мотивация долженствования (учеба как необходимый труд) оказалась в большей степени сходной для групп мальчиков и девочек, она незначительно изменяется при взрослении.